Environmental conditions associated with carbonate-bearing rocks in lower Hawksbill Gap, Jezero western fan, Mars - Rebecca M.E. Williams; Joel A. Hurowitz; Linda C. Kah; Gwénaël Caravaca; Sanjeev Gupta; Nicolas Mangold; Michelle E. Minitti; R. Aileen Yingst; Kyle Uckert; Roger C. Wiens; Michael Tice; Megan Kennedy Wu; et al. (Icarus, 2026)

Sigma-2 Receptor Antagonism Enhances the Neuroprotective Effects of Pridopidine, a Sigma-1 Receptor Agonist, in Huntington’s Disease - Jing Jin; Randal Hand; May Meltzer; Carmen Abate; Michal Geva; Michael R. Hayden; Christopher A. Ross (Molecular Neurobiology, 2026)

A large cracticine passerine (Aves, Artamidae, Cracticinae) from the Early Miocene, St Bathans Fauna of New Zealand - Trevor H. Worthy; R. Paul Scofield; Suzanne J. Hand; Michael Archer; Vanesa L. De Pietri (PalZ, 2025)
A large fossil passerine (Aves, Artamidae, Cracticinae, Miostrepera canora gen. et sp. nov.), of Early Miocene (19–16 Ma) age, is described based on a proximal and a distal humerus from the lower Bannockburn Formation near St Bathans in Otago, New Zealand. Referred material includes a previously reported scapula and, tentatively so, a distal tibiotarsus. This taxon is the largest passerine in the St Bathans Fauna, in which the total passerine diversity may include up to 17 species. The only other named passerine in this fauna is a tiny acanthisittid wren, Kuiornis indicator . Cracticines (currawongs, magpies and butcherbirds) were absent in the native avifauna of New Zealand during the late Quaternary but are represented by the introduced Australian Magpie Gymnorhina tibicen now. The group is widespread in Australia with a fossil record extending to the Early Miocene. The presence of a Strepera -like cracticine in the Early Miocene in New Zealand indicates overwater dispersal to and colonisation of Zealandia from Australia that we suggest was facilitated by the diverse flora in the subtropical environments of Zealandia at the time. The subsequent loss of cracticines from the Zealandian avifauna is correlated with the marked loss in floral diversity following the climate cooling in the Middle Miocene and during the subsequent Pleistocene glacial oscillations. Furthermore, we show that the osteological correlates of the origin of musculus humerotriceps pars dorsalis are shown to be more complex than presence or absence of a dorsal fossa on the humerus.

Early Miocene gull-like birds (Charadriiformes: Laridae) from New Zealand - Vanesa L. De Pietri; R. Paul Scofield; Suzanne J. Hand; Mike Archer; Alan J.D. Tennyson; Trevor H. Worthy (Geobios, 2025)

A synopsis of the Early Miocene St Bathans Fauna of New Zealand - Trevor H. Worthy; R. Paul Scofield; Vanesa L. De Pietri; Steven W. Salisbury; Werner Schwarzhans; Suzanne J. Hand; Michael Archer (Geobios, 2025)

Dust in the Critical Zone: North American case studies - J. Brahney; R.C. Heindel; T.E. Gill; G. Carling; J.M. González-Olalla; J. Hand; D.V. Mallia; J.S. Munroe; K. Perry; A.L. Putman; S.M. Skiles; B.R. Adams; et al. (Earth-Science Reviews, 2024)

Microbial interactions with phosphorus containing glasses representative of vitrified radioactive waste - C.L. Thorpe; R. Crawford; R.J. Hand; J.T. Radford; C.L. Corkhill; C.I. Pearce; J.J. Neeway; A.E. Plymale; A.A. Kruger; K. Morris; C. Boothman; J.R. Lloyd (Journal of Hazardous Materials, 2024)

Analytical solutions to evaluate the geothermal energy generation potential from sedimentary-basin reservoirs - Daniel T. Birdsell; Benjamin M. Adams; Paromita Deb; Jonathan D. Ogland-Hand; Jeffrey M. Bielicki; Mark R. Fleming; Martin O. Saar (Geothermics, 2024)

Knowledge, Perception, and Variables Influencing Consumption of Plant-based Protein Sources in Dining Halls Among Undergraduate Students at a Midwest University - V. Martinez Tenorio; R. Hand (Journal of the Academy of Nutrition and Dietetics, 2023)

Two new neoavian taxa with contrasting palaeobiogeographical implications from the early Miocene St Bathans Fauna, New Zealand - Trevor H. Worthy; R. Paul Scofield; Steven W. Salisbury; Suzanne J. Hand; Vanesa L. De Pietri; Michael Archer (Journal of Ornithology, 2022)
Two new neoavian landbirds are reported from the early Miocene St Bathans Fauna from New Zealand. Aegotheles zealandivetus sp. nov. is described from several bones, among which, notably, the tarsometatarsus shows more similarity to New Guinean taxa than to Australian—New Zealand species. Zealandornis relictus gen. et sp. nov. is described from a distal end of a humerus and placed in the new family Zealandornithidae, tentatively among the ‘higher landbirds’ Telluraves, with most similarity to coliiforms. The humerus is of similar size to that of species of Colius and its gracile shaft and very shallow sulcus scapulotricipitalis suggests reduced flying ability. The new species of Aegotheles reinforces the Australasian nature of the Zealandian fauna, while in contrast, Zealandornis relictus gen. et sp. nov. appears to have no close relatives. It is as distinct as Acanthisittidae and Strigopidae among birds, or Leiopelmatidae and Sphenodontidae among the herpetofauna, and like them, represents a similar relictual taxon. Together they confer a highly evolutionarily distinctive nature to the Zealandian fauna concomitant with a minimal 60 million years of isolation.

Utilising TMS-EEG to Assess the Response to Cerebellar-Brain Inhibition - R. Sasaki; B. J. Hand; W. Y. Liao; N. C. Rogasch; L. Fernandez; J. G. Semmler; G. M. Opie (The Cerebellum, 2022)
Cerebellar-brain inhibition (CBI) is a transcranial magnetic stimulation (TMS) paradigm indexing excitability of cerebellar projections to motor cortex (M1). Stimulation involved with CBI is often considered to be uncomfortable, and alternative ways to index connectivity between cerebellum and the cortex would be valuable. We therefore sought to assess the utility of electroencephalography in conjunction with TMS (combined TMS-EEG) to record the response to CBI. A total of 33 volunteers (25.7 ± 4.9 years, 20 females) participated across three experiments. These investigated EEG responses to CBI induced with a figure-of-eight (F8; experiment 1) or double cone (DC; experiment 2) conditioning coil over cerebellum, in addition to multisensory sham stimulation (experiment 3). Both F8 and DC coils suppressed early TMS-evoked EEG potentials (TEPs) produced by TMS to M1 ( P < 0.05). Furthermore, the TEP produced by CBI stimulation was related to the motor inhibitory response to CBI recorded in a hand muscle ( P < 0.05), but only when using the DC coil. Multisensory sham stimulation failed to modify the M1 TEP. Cerebellar conditioning produced changes in the M1 TEP that were not apparent following sham stimulation, and that were related to the motor inhibitory effects of CBI. Our findings therefore suggest that it is possible to index the response to CBI using TMS-EEG. In addition, while both F8 and DC coils appear to recruit cerebellar projections, the nature of these may be different.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

3D Morphometric Analysis Reveals Similar Ecomorphs for Early Kangaroos (Macropodidae) and Fanged Kangaroos (Balbaridae) from the Riversleigh World Heritage Area, Australia - Kaylene Butler; Kenny J. Travouillon; Alistair R. Evans; Laura Murphy; Gilbert J. Price; Michael Archer; Suzanne J. Hand; Vera Weisbecker (Journal of Mammalian Evolution, 2021)

Resubduction of lawsonite eclogite within a serpentinite-filled subduction channel - R. Tamblyn; M. Hand; L. Morrissey; T. Zack; G. Phillips; D. Och (Contributions to Mineralogy and Petrology, 2020)

Greenhouse gas emissions and extracellular enzyme activity variability during decomposition of native versus invasive riparian tree litter - Benjamin D. Duval; Heather D. Curtsinger; Aubrey Hands; Jamie Martin; Jennie R. McLaren; Daniel D. Cadol (Plant Ecology, 2020)

Assembly and characterisation of a unique onion diversity set identifies resistance to Fusarium basal rot and improved seedling vigour - Andrew Taylor; Graham R. Teakle; Peter G. Walley; William E. Finch-Savage; Alison C. Jackson; Julie E. Jones; Paul Hand; Brian Thomas; Michael J. Havey; David A. C. Pink; John P. Clarkson (Theoretical and Applied Genetics, 2019)
Key message A unique, global onion diversity set was assembled, genotyped and phenotyped for beneficial traits. Accessions with strong basal rot resistance and increased seedling vigour were identified along with associated markers. Abstract Conserving biodiversity is critical for safeguarding future crop production. Onion ( Allium cepa L.) is a globally important crop with a very large (16 Gb per 1C) genome which has not been sequenced. While onions are self-fertile, they suffer from severe inbreeding depression and as such are highly heterozygous as a result of out-crossing. Bulb formation is driven by daylength, and accessions are adapted to the local photoperiod. Onion seed is often directly sown in the field, and hence seedling establishment is a critical trait for production. Furthermore, onion yield losses regularly occur worldwide due to Fusarium basal rot caused by Fusarium oxysporum f. sp. cepae . A globally relevant onion diversity set, consisting of 10 half-sib families for each of 95 accessions, was assembled and genotyping carried out using 892 SNP markers. A moderate level of heterozygosity (30–35%) was observed, reflecting the outbreeding nature of the crop. Using inferred phylogenies, population structure and principal component analyses, most accessions grouped according to local daylength. A high level of intra-accession diversity was observed, but this was less than inter-accession diversity. Accessions with strong basal rot resistance and increased seedling vigour were identified along with associated markers, confirming the utility of the diversity set for discovering beneficial traits. The onion diversity set and associated trait data therefore provide a valuable resource for future germplasm selection and onion breeding.

Pomegranate dieback caused by Lasiodiplodia gilanensis in California - J. R. Úrbez-Torres; F. Peduto Hand; F. P. Trouillas; W. D. Gubler (European Journal of Plant Pathology, 2017)

Node position influences viability and contamination in hazelnut shoot explants - Charles R. Hand; Nami Wada; Virginia Stockwell; Barbara M. Reed (In Vitro Cellular & Developmental Biology - Plant, 2016)

Climate variables explain neutral and adaptive variation within salmonid metapopulations: the importance of replication in landscape genetics - Brian K. Hand; Clint C. Muhlfeld; Alisa A. Wade; Ryan P. Kovach; Diane C. Whited; Shawn R. Narum; Andrew P. Matala; Michael W. Ackerman; Brittany A. Garner; John S. Kimball; Jack A. Stanford; Gordon Luikart (Molecular Ecology, 2016)
Understanding how environmental variation influences population genetic structure is important for conservation management because it can reveal how human stressors influence population connectivity, genetic diversity and persistence. We used riverscape genetics modelling to assess whether climatic and habitat variables were related to neutral and adaptive patterns of genetic differentiation (population‐specific and pairwise F ST ) within five metapopulations (79 populations, 4583 individuals) of steelhead trout ( Oncorhynchus mykiss ) in the Columbia River Basin, USA . Using 151 putatively neutral and 29 candidate adaptive SNP loci, we found that climate‐related variables (winter precipitation, summer maximum temperature, winter highest 5% flow events and summer mean flow) best explained neutral and adaptive patterns of genetic differentiation within metapopulations, suggesting that climatic variation likely influences both demography (neutral variation) and local adaptation (adaptive variation). However, we did not observe consistent relationships between climate variables and F ST across all metapopulations, underscoring the need for replication when extrapolating results from one scale to another (e.g. basin‐wide to the metapopulation scale). Sensitivity analysis (leave‐one‐population‐out) revealed consistent relationships between climate variables and F ST within three metapopulations; however, these patterns were not consistent in two metapopulations likely due to small sample sizes ( N = 10). These results provide correlative evidence that climatic variation has shaped the genetic structure of steelhead populations and highlight the need for replication and sensitivity analyses in land and riverscape genetics.

Age constraints on the timing of iron ore mineralisation in the southeastern Gawler Craton - K. Lane; E. A. Jagodzinski; R. Dutch; A. J. Reid; M. Hand (Australian Journal of Earth Sciences, 2015)

Trade‐offs and utility of alternative RADseq methods: Reply to Puritz et al . - Kimberly R. Andrews; Paul A. Hohenlohe; Michael R. Miller; Brian K. Hand; James E. Seeb; Gordon Luikart (Molecular Ecology, 2014)
Puritz et al . provide a review of several RAD seq methodological approaches in response to our ‘Population Genomic Data Analysis’ workshop (Sept 2013) review (Andrews & Luikart 2014). We agree with Puritz et al . on the importance for researchers to thoroughly understand RADseq library preparation and data analysis when choosing an approach for answering their research questions. Some of us are currently using multiple RAD seq protocols, and we agree that the different methods may offer advantages in different cases. Our workshop review did not intend to provide a thorough review of RAD seq because the workshop covered a broad range of topics within the field of population genomics. Similarly, neither the response of Puritz et al . nor our comments here provide sufficient space to thoroughly review RAD seq. Nonetheless, here we address some key points that we find unclear or potentially misleading in their evaluation of techniques.

Identification of QTLs for morphological traits influencing waterlogging tolerance in perennial ryegrass (Lolium perenne L.) - Allison Pearson; Noel O. I. Cogan; Rebecca C. Baillie; Melanie L. Hand; Champa K. Bandaranayake; Stacey Erb; Junping Wang; Gavin A. Kearney; Anthony R. Gendall; Kevin F. Smith; John W. Forster (Theoretical and Applied Genetics, 2011)

Identification of genetic factors influencing salt stress tolerance in white clover (Trifolium repens L.) by QTL analysis - Junping Wang; Michelle C. Drayton; Julie George; Noel O. I. Cogan; Rebecca C. Baillie; Melanie L. Hand; Gavin A. Kearney; Stacey Erb; Tania Wilkinson; Nathaniel R. Bannan; John W. Forster; Kevin F. Smith (Theoretical and Applied Genetics, 2010)

Genetic map construction and QTL mapping of resistance to blackleg (Leptosphaeria maculans) disease in Australian canola (Brassica napus L.) cultivars - S. Kaur; N. O. I. Cogan; G. Ye; R. C. Baillie; M. L. Hand; A. E. Ling; A. K. Mcgearey; J. Kaur; C. J. Hopkins; M. Todorovic; H. Mountford; D. Edwards; et al. (Theoretical and Applied Genetics, 2009)

High-grade Paleoproterozoic reworking in the southeastern Gawler Craton, South Australia ∗ - R. Dutch; M. Hand; P. D. Kinny (Australian Journal of Earth Sciences, 2008)

Origin of metasedimentary and igneous rocks from the Entia Dome, eastern Arunta region, central Australia: a U – Pb LA-ICPMS, SHRIMP and Sm – Nd isotope study - B. P. Wade; M. Hand; D. W. Maidment; D. F. Close; I. R. Scrimgeour (Australian Journal of Earth Sciences, 2008)

Alpha e-taxonomy: responses from the systematics community to the biodiversity crisis - S. J. Mayo; R. Allkin; W. Baker; V. Blagoderov; I. Brake; B. Clark; R. Govaerts; C. Godfray; A. Haigh; R. Hand; K. Harman; M. Jackson; et al. (Kew Bulletin, 2008)

The reference genetic linkage map for the multinational Brassica rapa genome sequencing project - Su Ryun Choi; Graham R. Teakle; Prikshit Plaha; Jeong Hee Kim; Charlotte J. Allender; Elena Beynon; Zhong Yun Piao; Pilar Soengas; Tae Ho Han; Graham J. King; Guy C. Barker; Paul Hand; et al. (Theoretical and Applied Genetics, 2007)

Blue sucker stock characteristics in the upper Yazoo River basin, Mississippi, USA - G. R. Hand; D. C. Jackson (Fisheries Management and Ecology, 2003)
Blue sucker Cycleptus elongatus (L.) in the upper Yazoo River basin, Mississippi, USA was studied using overnight hoop net sets ( n = 4093) during 1988 and 1990–1998 to determine the influence of channel dredging. There were 264 blue suckers captured, ranging from 3 to 11 years of age. Length ranged from 265 to 700 mm and weight from 120 to 4700 g. Concurrent studies with smaller mesh hoop nets failed to capture any juvenile blue suckers. Catch‐per‐unit‐effort (CPUE: fish net −1 ) declined throughout the study in the Yalobusha River, a river subjected to channel dredging during 1988 and 1994. With the exception of limited hydraulic dredging in the Tallahatchie River, there was no dredging in the other Yazoo River tributaries, nor were there declines in blue sucker catch rates in these rivers. Throughout the upper Yazoo River basin, blue sucker stocks were dominated by adult fish, and there was little evidence of reproduction or recruitment. Conservation of the blue sucker in the upper Yazoo River basin should include actions that ensure the functional integrity of this floodplain river ecosystem and elimination of channel dredging throughout the basin.

Novel mutations in the 3' region of the polycystic kidney disease 1 (PKD1) gene - A.R. Afzal; M. Hand; E. Ternes-Pereira; A. Saggar-Malik; R. Taylor; S. Jeffery (Human Genetics, 1999)

Novel mutations in the 3' region of the polycystic kidney disease 1 (PKD1) gene - A.R. Afzal; M. Hand; E. Ternes-Pereira; A. Saggar-Malik; R. Taylor; S. Jeffery (Human Genetics, 1999)

Characterization of volume-sensitive organic osmolyte efflux and anion current in Xenopus oocytes - M. Hand; R. Morrison; K. Strange (The Journal of Membrane Biology, 1997)

Distribution of the bispyridinium oxime [14C] HI-6 in male and female rats - Paul M. Lundy; Brian T. Hand; Brian R. Broxup; George Yipchuck; Murray G. Hamilton (Archives of Toxicology, 1990)

The multipolar content of the human electrocardiogram - Leo G. Horan; R. Chris Hand; Nancy C. Flowers; Jennifer C. Johnson; Daniel A. Brody (Annals of Biomedical Engineering, 1976)